Performance analysis and optimal parameters of a direct evaporative pad cooling system under the climate conditions of Morocco. (March 2019) - Laknizi, Azzeddine; Mahdaoui, Mustapha; Ben Abdellah, Abdelatif; Anoune, Kamal; Bakhouya, Mohamed; Ezbakhe, Hassan
Abstract: In this study, a direct evaporative pad cooling system to be used for a poultry house is simulated under the climate conditions of six Moroccan cities. The objective is to optimize the parameters affecting the performance of the system for each city. The thermodynamic properties of humid air are extracted from the open source program CoolProp, and a computer program is used to perform a parametric study in order to find the impacts of the pad thickness and the frontal velocity on system's performance. Simulations have been conducted on cellulosic pad cooling and obtained results show that the system has the potential to lower the outdoor temperature during the hottest period with a coefficient of performance higher than 80, while the average rate of water consumption is higher than 3.3 kg per hour.